Transcriptional regulation of thylakoid galactolipid biosynthesis coordinated with chlorophyll biosynthesis during the development of chloroplasts in Arabidopsis - Kobayashi, Koichi; Fujii, Sho; Sasaki, Daichi; Baba, Shinsuke; Ohta, Hiroyuki; Masuda, Tatsuru; Wada, Hajime (Frontiers in Plant Science, 2014)
Biogenesis of thylakoid membranes in chloroplasts requires the coordinated synthesis of chlorophyll and photosynthetic proteins with the galactolipids monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG), which constitute the bulk of the thylakoid lipid matrix. MGD1 and DGD1 are the key enzymes of MGDG and DGDG synthesis, respectively. We investigated the expression profiles of MGD1 and DGD1 in Arabidopsis to identify the transcriptional regulation that coordinates galactolipid synthesis with the synthesis of chlorophyll and photosynthetic proteins during chloroplast biogenesis. The expression of both MGD1 and DGD1 was repressed in response to defects in chlorophyll synthesis. Moreover, these genes were downregulated by norflurazon-induced chloroplast malfunction via the GENOMES-UNCOUPLED1-mediated plastid signaling pathway. Similar to other photosynthesis-associated nuclear genes, the expression of MGD1 and DGD1 was induced by light, in which both cytokinin signaling and LONG HYPOCOTYL5-mediated light signaling played crucial roles. The expression of these galactolipid-synthesis genes, and particularly that of DGD1 under continuous light, was strongly affected by the activities of the GOLDEN2-LIKE transcription factors, which are potent regulators of chlorophyll synthesis and chloroplast biogenesis. These results suggest tight transcriptional coordination of galactolipid synthesis with the formation of the photosynthetic chlorophyll-protein complexes during leaf development. Meanwhile, unlike the photosynthetic genes, the galactolipid synthesis genes were not upregulated during chloroplast biogenesis in the roots, even though the galactolipids accumulated with chlorophylls, indicating the importance of post-transcriptional regulation of galactolipid synthesis during root greening. Our data suggest that plants utilize complex regulatory mechanisms to modify galactolipid synthesis with chloroplast development during plant growth.